2014
DOI: 10.1111/jep.12284
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial within a trial of yellow ‘post‐it notes’ did not improve questionnaire response rates among participants in a trial of treatments for neck pain

Abstract: Yellow post-it notes do not enhance questionnaire return rates for participants in a randomized trial of neck pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…A single embedded trial will often not have the statistical power to detect a modest difference if there truly was one present; therefore, we have a strategy of repeating our SWATs in order to conduct meta-analyses to strengthen the evidence base. With respect to newsletters sent prior to questionnaires, our previous trial showed a small absolute difference in favour of the intervention, which was borderline statistically significant (p=0.05) 5 , whereas our two previous studies of Post-it® notes 7, 8 produced identical, non-statistically significant ORs (0.97) favouring the control group (no Post-it® note).…”
Section: Introductioncontrasting
confidence: 59%
“…A single embedded trial will often not have the statistical power to detect a modest difference if there truly was one present; therefore, we have a strategy of repeating our SWATs in order to conduct meta-analyses to strengthen the evidence base. With respect to newsletters sent prior to questionnaires, our previous trial showed a small absolute difference in favour of the intervention, which was borderline statistically significant (p=0.05) 5 , whereas our two previous studies of Post-it® notes 7, 8 produced identical, non-statistically significant ORs (0.97) favouring the control group (no Post-it® note).…”
Section: Introductioncontrasting
confidence: 59%
“…The evidence for an improvement in response rates in questionnaire studies has to date had mixed results, with response rates in students showing a significant improvement and a study in a health care setting showing no improvement . Our trial, a ‘trial within trials’ found no significant difference in response rates between the use of a Post‐it® note or control for the 4 month follow‐up questionnaires for older aged people with depressive symptoms.…”
Section: Discussionmentioning
confidence: 61%
“…The findings of this ‘trial within trials’ study supports the evidence from Tilbrook et al . who also found no significant effects of improvement in response rates using a Post‐it® note intervention in a healthcare research setting.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have so far found that electronic reminders are effective, [10] newsletters to trial participants are promising (one trial showing effectiveness, another in progress), [11] and sticky notes may be ineffective (one small trial showing no effect with others in progress). [12] For recruitment, we have tested or are testing different designs of patient information sheets, publicity, prerecruitment notification, envelope colour, and additional centre visits by a trial coordinator.…”
Section: Trials Within Trialsmentioning
confidence: 99%